2013
DOI: 10.1093/annonc/mdt109
|View full text |Cite
|
Sign up to set email alerts
|

Temsirolimus combined with sorafenib in hepatocellular carcinoma: a phase I dose-finding trial with pharmacokinetic and biomarker correlates

Abstract: The MTD of sorafenib plus temsirolimus in HCC was lower than in other tumor types. HCC-specific phase I studies are necessary. The observed efficacy warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 38 publications
0
45
0
Order By: Relevance
“…The median overall survival was 19.3 mo (95%CI: 13.4-25.1 mo), and the median time to progression was 6.77 mo (95%CI: 2.3-11.1 mo). Although a few studies have shown that there is some evidence of synergistic anticancer activity, early-phase clinical studies of mTOR inhibitors plus sorafenib for advanced HCC reported ambivalent findings, which were the results of increased toxicity (e.g., hand-foot syndrome) in combination therapy [51,52] . In a recent study from Italy, the outcomes of sorafenib treatment for post-LT HCC recurrence were significantly better than those of best medical care [median patient survival from recurrence: 21.3 mo vs 11.8 mo, hazard ratio (HR) = 5.2, P = 0.0009; median patient survival from untreatable presentation or progression: 10.6 mo vs 2.2 mo, HR = 21.1, P < an overall survival rate of 90% at a median follow-up period of 275 d (range: 32-677 d) [33] .…”
Section: Treatment For Multiple Recurrencementioning
confidence: 99%
“…The median overall survival was 19.3 mo (95%CI: 13.4-25.1 mo), and the median time to progression was 6.77 mo (95%CI: 2.3-11.1 mo). Although a few studies have shown that there is some evidence of synergistic anticancer activity, early-phase clinical studies of mTOR inhibitors plus sorafenib for advanced HCC reported ambivalent findings, which were the results of increased toxicity (e.g., hand-foot syndrome) in combination therapy [51,52] . In a recent study from Italy, the outcomes of sorafenib treatment for post-LT HCC recurrence were significantly better than those of best medical care [median patient survival from recurrence: 21.3 mo vs 11.8 mo, hazard ratio (HR) = 5.2, P = 0.0009; median patient survival from untreatable presentation or progression: 10.6 mo vs 2.2 mo, HR = 21.1, P < an overall survival rate of 90% at a median follow-up period of 275 d (range: 32-677 d) [33] .…”
Section: Treatment For Multiple Recurrencementioning
confidence: 99%
“…Similarly, an incremental activation of mTOR was detected in HCC, dysplastic nodules and non-neoplastic surrounding tissues when compared with normal livers, with the highest expression being in HCC [57,58]. In HCCs, activation of the mTOR signaling has been associated with poor differentiation, high TNM and BCLC staging, high AFP, intra-hepatic metastasis, vascular invasion, angiogenesis, high proliferation index and post-transplant recurrence; whereas inhibition of mTOR could suppress tumor growth and sensitize tumor cell to chemotherapy or other targeted therapies [53,54,56,57,[59][60][61][62]. In several preclinical studies, liver-specific TSC1 knockout mice showed constitutively elevated mTOR signaling and developed sporadic HCC [38,55,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…118 Temsirolimus: different phase I-II trials resulted in no favorable benefits of this combination. [119][120][121] …”
Section: Sorafenib Plus Mtor Inhibitorsmentioning
confidence: 99%